Comparative Performance and Daily Light Integral Requirements of Warm‐Season Turfgrasses in Different Seasons. Issue 4 (18th May 2017) - Zhang, Jing; Glenn, Brian; Unruh, J. Bryan; Kruse, Jason; Kenworthy, Kevin; Erickson, John; Rowland, Diane; Trenholm, Laurie
Abstract : Shade or reduced sunlight poses a major challenge for maintaining acceptable turfgrass quality. The quantification of daily light integral (DLI, mol m −2 d −1 ) requirement could help to identify shade‐tolerant germplasm. The objectives of this study were (i) to compare turf performance, and (ii) to determine seasonal DLI requirement of 12 warm‐season turfgrass cultivars in response to varying levels of shade. A greenhouse study that included three experiments was conducted in spring (30/20°C), summer (35/25°C), and winter (25/15°C) months. Shade levels providing 33, 61, and 92% reductions in photosynthetic photo flux were imposed. Twelve cultivars from nine species were evaluated for turfgrass quality (TQ), normalized difference vegetation index, and shoot biomass production over 8 wk. The DLI requirement was obtained through nonlinear regression between DLI and TQ. Most warm‐season turfgrass species maintained acceptable TQ up to 33% shade. 'TifGrand' and 'Tifway' bermudagrass [ Cynodon dactylon (L.) Pers × C. transvaalensis Burtt‐Davy] required each relatively higher DLI ranging from 9.2 (winter) to 21.4 (summer) mol m −2 d −1 . Zoysiagrass ( Zoysia spp.) cultivars maintained acceptable TQ up to 61% shade, with the lowest DLI requirements ranging from 5.9 (winter) to 10.9 (summer) mol m −2 d −1 . The DLI requirements for the tested grasses were lower in winter (5.9–9.9 mol m −2 d −1 ) than in spring (9.4–17.4 mol m −2 d −1 ) and summer (9.9–21.4 mol m −2 d −1 ). 'Argentine' bahiagrass ( Paspalum notatum Flugge) had an increased DLI requirement relative to other entries in summer months.